Diagnostic dilemma in autoinflammatory disease in two patients: does the name matter? - Gülhan, Bora; Büyükcam, Ayşe; Touitou, Isabelle; Özen, Seza (The Turkish Journal of Pediatrics, 2013)
The systemic autoinflammatory diseases are inflammatory disorders characterized by uncontrolled inflammation of the innate immune system. A common monogenic autoinflammatory disease is familial Mediterranean fever (FMF), associated with mutations in the MEFV gene. Another autoinflammatory disease group is cryopyrin-associated periodic syndromes (CAPS), which are characterized by urticarial rash and mutations of the gene NLRP. Systemiconset juvenile idiopathic arthritis (soJIA) is classified as a multifactorial autoinflammatory disease. We report two cases of systemic autoinflammatory disease with homozygous E148Q mutation in the FMF gene. They had unusual features, such as urticarial rash, non-erysipeloid erythema, lymphadenopathy, and hepatosplenomegaly, and neurological findings in one. These patients met the "definition" criteria for FMF with two mutations in the MEFV gene. They fit the "description" criteria for CAPS with their fever, urticaria, and other clinical features. They also met the "classification" criteria for soJIA, with the fever, rash, arthritis, and accompanying systemic features.